Comparison theorems for some nonsymmetric classes of functions - Motornaya, O. V.; Motornyi, V. P. (Ukrains’kyi Matematychnyi Zhurnal, 2008)
We prove comparison theorems of the Kolmogorov type for some nonsymmetric classes of functions.